Disain Mesin Pengaduk Pakan Puyuh Yang Dilengkapi Dengan Komponen Penyemprot Cairan Fermentasi - Ruzita Sumiati; Fahri Reza; Nandi Pinto; Adriansyah Adriansyah; Yuli Yetri (METAL: Jurnal Sistem Mekanik dan Termal, 2022)
This study was carried out to deal with reducing feed cost and provide high quality poultry feed for the local breed of quail  through the provision of feed mixer machines equipped with fermentation equipment.  Mixing feed poultry using machines is much faster, accurate and less energy consuming compered with manual mixing. Poultry  feed  mixing  machine  was  designed,  fabricated  and  tested. The  machine  consists  of  two function as mixing and fermented liquid spray. The  design  computations  to  handle  a  400 Kg  mass  of  feed and 4 L of fermented liquid. The machine was tested using afeed components divided into 170 kg for Maize bran, 120 kg for bran, 2 kg for mineral, 136  kg  for  Bone  meal , 2  kg  for  Salt and 4L fermented liquid replicated twice at four mixing durations of 4, 8, 12 and 16 min. The perfect homogenious mixing was got in 16 min